Protective cellular and humoral immune responses to Edwardsiella tarda in flounder (Paralichthys olivaceus) immunized by an inactivated vaccine. (September 2022) - Wu, Xiaoyan; Xing, Jing; Tang, Xiaoqian; Sheng, Xiuzhen; Chi, Heng; Zhan, Wenbin
Abstract: Protection is crucial for a vaccine. In this study, flounder was inoculated with an inactivated Edwardsiella tarda for 5 weeks then challenged with E. tarda, after that, the protective cellular and humoral immune responses were studied using specific antibodies against CD4, CD8 and IgM, respectively, previously produced in our lab. And then gene transcription, relative percent survival (RPS), innate enzyme activities and histopathology were investigated. The results showed that, in the vaccine group, the percentage of CD4 + T and CD8 + T lymphocytes increased significantly, peaking on 7th post challenge day. The percentage of IgM + B lymphocytes increased significantly first and peaked at 2nd post challenge week. Total and specific antibodies significantly increased and peaked at 3rd week. The mRNA expressions of MHCIα, MHCIIα, CD4–1 and CD8α were significantly upregulated. In the meantime, alkaline phosphatase, acid phosphatase, superoxide dismutase and lysozyme significantly rose and reached to the maximum. The RPS was 54.76 ± 1.92%. The bacterial load in spleen and head kidney was lower in the vaccine group than that of PBS group. These data illustrated that T lymphocyte subsets, B lymphocytes, immune enzymes were induced strong protection against E. tarda for flounder. These results revealed a strong support protection of the vaccine from four aspects, and provided a new perspective for the evaluation of fish vaccines. Highlights: T and B lymphocytes were markedly increased in vaccinated flounder post challenge. Specific antibody in vaccinated flounder increased markedly at 3rd post challenge week. Four immune genes were upregulated after E. tarda challenge. Activities of AKP, ACP, SOD and lysozyme rose markedly on 7th post challenge day. Loads of E. tarda reduced in head kidney and spleen of vaccinated flounder.